An Updated Review on Diuretic Plants-2012 - Vanamala, Usha (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTIndia is one of the richest floristic regions of the world and has been a source of plants and their products since antiquity and man uses them in different ways according to his needs, particularly as food or as medicine. There is rising interest of herbal drugs in the health and their benefits. The beneficial reason is that they might offer a natural safeguard against the development of certain conditions and be a reputed treatment for some diseases or ailments. One major class of clinical medicines that are used to lower the blood pressure are known as diuretics and they work by increasing the volume of urinary excretion as well as the amount of sodium in urine from our body. There are a large number of studies which supports the diuretic effects of traditional herbal medicines. The aim of this review is to highlight the work on diuretics of plant origin. The present paper also involves various plant drugs and their bioactive extracts involved in diuretic mechanism. This article may help investigators to identify medicinal plants responsible for diuretic activity.